PERHITUNGAN IDLE CAPACITY DENGAN MENGGUNAKAN CAM-I CAPACITY MODEL DALAM RANGKA EFISIENSI BIAYA PADA PT X - Muammar Aditya (Faculty of Economic and Business, 2014)
Aim for this research are to analyze capacity cost which incure from company production machines and human resources whose operate the production machine using CAM-I capacity model. CAM-I capacity model is an approach which focus upon how to manage company resources. This research initiated at PT X which focus to production activity that used small mixer machine, extruder machine, oven drying machine, enrober machine, pan coting machine which consist of hot and cold pan coating machine, and packing machine which consist of vertical packing machine and horizontal packing machine as well as human resources that operates those machine. This research focus on rate capacity, productive capacity, idle capacity, and nonproductive capacity to measure capacity cost. Result of this research shows most of the capacity owned by either by production machine or human resources are not utilized to its maximum potential. There are need to reduce capacity cost owned by production machine and human resoures to increase the product sales but if its unachieveable there will be need to increase efficiency from production machine and human resources by reducing their quantityDOI: 10.15408/ess.v4i1.1961